Comparison of Five Different Criteria for Diagnosis of Subclinical Hypothyroidism in a Large-Scale Chinese Population - Zheng, Yan-song; Dong, Sheng-yong; Gong, Yan; Wang, Jia-hong; Wang, Fei; Zeng, Qiang (Frontiers in Endocrinology, 2022)
Background: Several different criteria for subclinical hypothyroidism (SCH) have been used in the literature, but the performance of these criteria was unknown. Objective: This retrospective study was to evaluate the diagnostic criteria for SCH. Methods: Eligible participants were based on centration of thyroglobulin antibodies (TG-Ab), thyroid peroxidase antibodies (TPO-Ab), and five thyroid-related hormones including total thyroxine (TT4), total triiodothyronine (TT3), free thyroxine (FT4), free triiodothyronine (FT3), and thyroid-stimulating hormone (TSH). Euthyroid individuals were identified via specific criteria. Five different SCH diagnostic criteria were compared based on the distributions of those indicators. An appropriate TSH cut-off value was reconsidered. Results: The study included 145,015 participants. The number of SCH cases diagnosed using criterion 5 was significantly different compared to the cases diagnosed using criteria 1-4 (P<0.05) and had the highest positive proportions of TG-Ab and TPO-Ab. Analysis of 60,515 subjects with normal other thyroid hormones revealed a median TSH concentration of 2.04 mIU/L, and the P2.5–P97.5 CI was 0.48-7.03 mIU/L. When the threshold for TSH elevation was elevated from ≥4.5 mIU/L to ≥6.50 mIU/L, the number of diagnosed SCH cases decreased from 7.30% to 2.09% and the proportions of positive TG-Ab and TPO-Ab increased from 23.69% and 24.07% to 33.75% and 35.06%, respectively (P<0.01). Conclusions: Combination of an elevated TSH and normal TT3, TT4, FT3, and FT4 concentrations is a must for the diagnosis of SCH. A new TSH threshold should be identified for better patient monitoring and management, according to the real-world characteristics of TSH distribution in Chinese population.